Manual on drilling, sampling, and analysis of coal - Luppens, James A. 1946-; Wilson, Stephen E.; Stanton, Ronald W. (ASTM, 1992)
Annotation Compiles general guidelines (adaptable to various specific needs) for drilling coal. Intended for use as the basic outline for a company or agency's own field manual. Abundant references are provided. Member price, $32. Annotation c. by Book News, Inc., Portland, Or.
"ASTM publication code no. (PCN): 28-011092-13."
Keywords: Coal -- Sampling.; Borings.; elektronické knihy; electronic books